SLEEP DISTURBANCE AFTER TRAUMATIC BRAIN INJURY: NEW INSIGHT - Desak Ketut Indrasari Utami; Faldi Yaputra (MNJ (Malang Neurology Journal), 2023)
Disruptions in sleep-wake cycles are particularly prevalent after a Traumatic Brain Injury (TBI). Sleep disruptions may occur as a main impact of brain damage or as a result of other neuropsychiatric sequelae of TBI, such as anxiety disorder, depressive disorders, substance abuse, chronic pain, and/or medication consumption. Chronic discomfort (headache and broad pain, presumably of central origin) and/or sleep difficulties (insomnia, disturbed breathing, periodic limb movements) occur in about one in five people with TBI. Disruptions in sleep-wake cycles linked with TBI need therapy. Although data specific to individuals with TBI is currently limited, cognitive-behavioral treatment and medication may be beneficial in alleviating sleep-wake problems in people who have sustained a TBI. This article aims to raise awareness of sleep disturbance after TBI to enhance diagnosis, assessment, and therapy and disclose new research opportunities.